(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The analysis of the brand extensions dataset spanning from 2009 to 2023 offers valuable insights into the evolving landscape of research in this particular field. This dataset, composed of 478 documents from 198 sources, sheds light on the dynamics of academic inquiry. Despite a slight negative annual growth rate of -0.23%, these documents exhibit significant scholarly influence, with an average of 20.18 citations per document and a cumulative reference count of 21,273. This emphasizes the field’s breadth and the widespread recognition of its research contributions within the academic community. A notable aspect of this dataset is the extensive authorship, featuring 1,012 authors and a clear trend of collaboration, as indicated by an average of 2.6 co-authors per document. International co-authorships, constituting 25.52% of all collaborations, underscore the global reach and collaborative spirit characterizing research in brand extensions. The preference for articles as the primary mode of sharing findings is evident, with all 478 documents adopting this format. However, the annual trend of publications showcases fluctuations, with peak years in 2010 and 2017, while 2011 and 2018 marked lower research output, signifying the changing interests and focus within the field. The analysis extends to ranking prominent contributors, where authors like Dwivedi A.; Merrilees B., Dens N.; De Pelsmacker P., Freling T.H.; Crosno J.L.; Henard D.H. stand out. Furthermore, it identifies influential journals such as the “Journal of Brand Management”, “Journal of Business Research”, and “Journal of Product and Brand Management”, which serve as significant platforms for disseminating research. Institutional prominence is also evident, with the Department of Business Administration at National Chengchi University, Taipei, and the Department of Marketing at the Norwegian School of Management, Oslo, emerging as key research centers. International collaboration among countries plays a pivotal role in shaping the research landscape, with the United States, China, and India contributing significantly. This collaborative spirit reflects the global nature of research in the field of brand extensions. In conclusion, this analysis equips researchers with a comprehensive understanding of the brand extension research landscape, helping to identify key contributors, influential sources, and opportunities for fruitful collaboration in this dynamic and globally connected field.